DESIGN AND PROTOTYPING OF ELECTRIC CARRYING TRACTORS - Rizayana, Farid; Kwintarini, Widiyanti; Hermawan, Muhammad Reza; Bayuseno, Athanasius P; Jamari, Jamari (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2023)
Locations with hard-to-reach access make people living in 3T (Terluar/Front, Terpencil/Remote, Terbelakang/Backward) areas unable to enjoy quality fuel oil (BBM) at affordable prices. This research provides solutions for people in remote areas and communities in the 3T area to utilize agricultural equipment without dependence on fuel. The agricultural equipment in question is a Multifunctional Portable Tractor driven by an electric motor, using a battery. Batteries are recharged from solar sources through solar panels, water turbines and wind turbines. The research method used adopts the